A survey to ascertain the Sentimental inclination of the Average Capital Market investor in Kenya. - W. Chesoli, Dr. Joshua (IJRDO - Journal of Business Management, 2018)
For a little over three years (2004-2007), the Kenyan stock market was on a roller coaster, maintaining a sustained bullish trend. Billions of funds from all shades and characters of investors entered the market as quantum gains were reaped by way of capital appreciation. Between 2005 and 2007, investors enjoyed an average return of 54% capital appreciation (NSE-ASI: 2005-2007). In 2007, for instance, investors raked in a 75% return on their portfolios, as the All-shares Index, an indicator of market growth, climbed from 33, 189.30 year-end 2006 to 57,990.22 year-end 2007. The market capitalization climbed from Ksh. 5.12 trillion to Ksh. 13.30 trillion, a 159.7% appreciation. Nowhere in the world were these kinds of returns made. Then, abruptly, the party ended and many were caught with gargantuan hangovers that have refused to go. Between April 2008 and March 2009, the market has depreciated by over 70%. And the loss has continued to mount. The new face of the market is characterized by the following challenges: Increasing awareness of capital market opportunities is quite distant from the sophisticated expertise and skill required and possessed by analysts to review stocks and the market in general; Most of the over Ksh. 1.0 trillion loss in stock dealings in 2008/09 were borne by new entrants who were taken in by the rumble of quick gain in the midst of high volatility; The nature of the boom and burst experienced in the capital market bellies the novice, crowd mentality syndrome, greed, and profit seeking investment attitude devoid of strategic entry and exit stock trading approach. The average Kenyan investor is said not to be prepared for the market in terms of the required psychological balance in the face of inherent market risks. A survey of individual investors and Asset Managers was carried out to ascertain the psychological or sentimental inclination of the average capital market investor especially Kenyan investor. The questionnaire was the major survey instrument. The key finding of this study is that stock investment in Kenya is largely driven by sentiments or the bandwagon effect and the sentiments are not supported by any fundamentally or technically verifiable strategy. The stock market can be seen as an engine of discovery that reflects sentiments and emotions, rather than seen as a mathematical abstraction.